Assets Accounting as the Way of Accountability in the Management of Local Government Assets - La Ode Anto, Alimuddin, Grace T. Pontoh, Tuti Dharmawati (International Journal of Advanced Science and Technology, 2020)
Provision of complete and readily available financial statements (assets) and with adequate accessibility for all information users determines the degree of transparency and accountability in local financial management. Public sector accountability has undergone a very fundamental change by emphasizing efforts to improve the role of accounting system in evaluating and measuring the performance of both financial and service performance, encouraging the quality of disclosure, and communicating the results to all stakeholders. This study aims to reveal the meaning of asset accounting that is understood by the local financial management actors. In this study the researcher uses an interpretive paradigm with a phenomenological approach. The results show that asset accounting is interpreted as a form of public accountability for asset management. in an effort to provide adequate and useful information on controlling/supervising local government assets. This is considered very good and important in order to realize more transparent and accountable local government asset management. It is understood that good local government asset accounting is very useful in asset management. Assets will be easier to monitor and their use can be more effective and efficient in providing services to the community.In this way the local government believes that asset management and reporting is becoming more transparent and accountable.